Pengaruh Pengungkapan Akuntansi Lingkungan Dan Kinerja Lingkungan Terhdapa Nilai Perusahaan Pada Perusahaan Pertanian Yang Terdaftar Di Bei Tahun 2017-2023 - Oktaviani, Marista; Setiawan, Adhar Putra; Surahman, Dedy (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
ABSTRACT This research aims to examine and analyze the influence of environmental accounting disclosures and environmental performance on company value in the largest agricultural companies listed on the Indonesia Stock Exchange for the 2016-2022 period. This research is quantitative research. The research samples were 5 companies that were among the largest companies on the IDX, observation years 2016-2022 which were carried out using purposive sampling techniques. The analysis technique is carried out using multiple linear regression. The research results show that the environmental accounting disclosure variables and environmental performance have a significant effect on company value